Lakulisa/Urdhvareta-Shiva - Temples of India Project Team (Jio Institute, 2024)
This Shaiva figure was possibly part of a deva-kostha or sculptural niche placed on the walls of the now-lost Shaiva shrine. The four-armed seated figure holds a trident and a staff in its upper two hands, while the lower two hands are significantly damaged. The figure is ithyphallic and represents the Urdhvareta aspect of Shiva, signifying full control over vital energies through ascetic vigour. This is likely an image of Lakulisa, the preceptor of the doctrine of Pashupata tradition. Given that the Harshnath Temple was clearly under the control of and likely erected by the ascetics of the Lakulisa-Pashupata tradition, the depiction of Lakulisa on temple walls comes as no surprise.